Clinical evaluation of patients with benign prostatic hyperplasia, treated with the natural product Calprost®: a randomized, controlled study - Magnelis Machado-Leiva; Daise Jiménez-Rodríguez; Tatiana Festary-Casanovas; Deydree C. Silveira-Pacheco; Emilio S. Barroso-de la Cruz; Mariela Suárez-Reyes; Genma Salas-Cruz; Haydee Wong-Arocha; Roberto Fernández-Viera; Ángela D. Tuero-Iglesias; René Delgado-Hernández; Idrian García-García; et al. (GarVal Editorial Ltda., 2016)
Context: Benign Prostatic Hyperplasia (BPH) is a common disease that course with Lower Urinary Tract Symptoms (LUTS), mainly in over 50 years-old men. Commonly indicated drugs such as alpha adrenergic-blockers are life-treatment with some adverse reactions. Center for Drug Research and Development produce a microencapsulated lipophilic extract of pumpkin seed oil (Calprost®) with anti-androgenic, anti-inflammatory, antioxidant, antiproliferative and diuretic properties. Aims: To evaluate the effect and safety of Calprost® in patients with BPH and LUTS. Methods: A multicenter, randomized, controlled, open exploratory clinical trial was conducted. Two experimental groups, study group (Calprost®, 140 mg daily) (n=81), and control group (terazosin, 2 mg daily) (n=50) were conformed. All the patients were treated during three months. Efficacy was evaluated through International Prostate Symptoms Score (IPSS), residual bladder volume and prostate volume. Results: Most of the included patients (74.0%) were white skin color and their mean age was 66 yrs. Fifteen patients, nine of them from terazosin group, withdraw the trial voluntarily. A significant reduction in the overall IPSS scale was obtained for both groups. Nevertheless, some obstructive (intermittency, straining) and irritative (frequency, urgency) urinary symptoms decreased more markedly in the Calprost® group being milder. Median residual and prostatic volumes decreased significantly (p=0.048 and p=0.002, respectively) only into the Calprost® group. Most of the adverse events were recorded in the terazosin group (79.4%), where postural hypotension prevailed. Conclusions: The natural product Calprost® was probed as a successful treatment of patients with BPH/LUTS, being also well-tolerated.